Synoptic Variability in Satellite Altimeter‐Derived Radar Freeboard of Arctic Sea Ice. Issue 2 (20th January 2023) - Nab, Carmen; Mallett, Robbie; Gregory, William; Landy, Jack; Lawrence, Isobel; Willatt, Rosemary; Stroeve, Julienne; Tsamados, Michel
Abstract: Satellite observations of sea ice freeboard are integral to the estimation of sea ice thickness. It is commonly assumed that radar pulses from satellite‐mounted Ku‐band altimeters penetrate through the snow and reflect from the snow‐ice interface. We would therefore expect a negative correlation between snow accumulation and radar freeboard measurements, as increased snow loading weighs the ice floe down. In this study we produce daily resolution radar freeboard products from the CryoSat‐2 and Sentinel‐3 altimeters via a recently developed optimal interpolation scheme. We find statistically significant ( p < 0.05) positive correlations between radar freeboard anomalies and modeled snow accumulation. This suggests that, in the period after snowfall, radar pulses are not scattering from the snow‐ice interface as commonly assumed. Our results offer satellite‐based evidence of winter Ku‐band radar scattering above the snow‐ice interface, violating a key assumption in sea ice thickness retrievals. Plain Language Summary: Arctic sea ice thickness is often estimated using radar pulses from satellite‐mounted Ku‐band altimeters, which retrieve the radar freeboard . This is a proxy for the height of the ice surface above the waterline. Ku‐band radar pulses are widely assumed to penetrate through the overlying snowpack and reflect from the top of the sea ice. This means that increased snow loading on a sea ice floe is expected to reduce its radar freeboard, as the snow weighs the sea ice down. We produce daily resolution pan‐Arctic radar freeboard data sets from CryoSat‐2 and Sentinel‐3 retrievals. Using these new products, we find that an increased snow load often increases the radar freeboard, suggesting that the radar pulses are not reflecting off the ice surface. This could explain why satellite‐based sea ice thickness estimates don't always match in situ observations. Key Points: We reveal synoptic‐scale positive correlations between snow accumulation and Ku‐band radar freeboard change These correlations indicate that the conventional assumption of full radar‐wave penetration of the snowpack does not always hold true This sensitivity in freeboard estimates to snow accumulation introduces synoptic variability into satellite estimates of sea ice thickness